2017
DOI: 10.47604/ijfa.260
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure on the Cost of Capital of Firms Listed at the Nairobi Securities Exchange, Kenya

Abstract: Purpose: The purpose of this study is to investigate the effects of CS on the cost of capital of organizationslisted at the NSE. Kenya.Methodology:The study adopted a descriptive research design. The target population for this study were the 41 listed companies on the NSE which were drawn from a list of 65 after applying various exclusion and inclusion criteria. A census of 41 firms was therefore used. Secondary Data for the year 2010 to 2014 was collected from the NSE handbook. Data collected was analysed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Zhou et al (2016) focused their research on the sensitivity of the cost of equity to leverage deviation and their results confirm theoretical predictions that the cost of equity is positively related to leverage deviation. Nicodemus (2017) revealed that the relationship between capital structure and total costs of capital is determined by an increase when the debt ratio increases in the capital structure (considering specific industry sectors). A sample of 41 enterprises was selected for the study and a simple correlation was used to measure the relationship between the two variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhou et al (2016) focused their research on the sensitivity of the cost of equity to leverage deviation and their results confirm theoretical predictions that the cost of equity is positively related to leverage deviation. Nicodemus (2017) revealed that the relationship between capital structure and total costs of capital is determined by an increase when the debt ratio increases in the capital structure (considering specific industry sectors). A sample of 41 enterprises was selected for the study and a simple correlation was used to measure the relationship between the two variables.…”
Section: Literature Reviewmentioning
confidence: 99%